Jigsaw Learning: Peningkatan Sikap dan Prestasi Belajar Siswa pada Materi Differensial di MA Ali Maksum - Tusilah, Tusilah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to determine the improvement of learning attitudes and achievement on differential material with a Jigsaw type cooperative learning model. This study uses classroom action research methods carried out in two cycles including planning, implementation, observation, and reflection activities. The subject of the study was a student of class XI IPS C Madrasah Aliyah Ali Maksum Yogyakarta. Data collection techniques are carried out by observation, interviews, tests, questionnaires, and documentation. Data analysis using qualitative descriptive analysis techniques. The results showed that students' attitudes and achievement in mathematics learning increased after the application of the Jigsaw type cooperative learning model. The percentage of increase in student learning attitudes in cycle I and cycle II were 4.84%. In cycle I, aspects of learning attitudes were obtained on average by 66.14% to 69.34% in cycle II. Meanwhile, student achievement increased by 7.80% from 72.56% in cycle I to 76.5% in cycle II.